The (d, 6Li) reaction on 64 66 68 Zn isotopes at 25.25 Mev - Ceballos, Alberto E.; Erramuspe, Hugo; Ferrero, A. M. J.; Sametband, M. J.; Testoni, Juan; Bés, Daniel; Maqueda, E. E. (North Holland Publishing, 1973)
Fil: Ceballos, Alberto E. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina